Methods for Imaging Renin-Synthesizing, -Storing, and -Secreting Cells - Daniel Casellas (International Journal of Hypertension)
Renin-producing cells have been the object of intense research efforts for the past fifty years within the field of hypertension. Two decades ago, research focused on the concept and characterization of the intrarenal renin-angiotensin system. Early morphological studies led to the concept of the juxtaglomerular apparatus, a minute organ that links tubulovascular structures and function at the single nephron level. The kidney, thus, appears as a highly “topological organ” in which anatomy and function are intimately linked. This point is reflected by a concurrent and constant development of functional and structural approaches. After summarizing our current knowledge about renin cells and their distribution along the renal vascular tree, particularly along glomerular afferent arterioles, we reviewed a variety of imaging techniques that permit a fine characterization of renin synthesis, storage, and release at the single-arteriolar, -cell, or -granule level. Powerful tools such as multiphoton microscopy and transgenesis bear the promises of future developments of the field.